2016
DOI: 10.20506/rst.35.1.2430
|View full text |Cite
|
Sign up to set email alerts
|

Use of genomics to track bovine tuberculosis transmission

Abstract: The control of any infectious disease of livestock is made more difficult by the presence of a wildlife reservoir, as the reservoir is often poorly observed and difficult to manage. This problem is particularly acute for bovine tuberculosis (bTB) because the long duration of infection and low levels of infectiousness make tracing the sources of infection difficult. For over 30 years, the process of contact tracing has been aided by the exploitation of molecular markers in the pathogen, but this has largely onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 100 publications
2
34
0
Order By: Relevance
“…Recent publications have shown the value of single nucleotide polymorphism (SNP) analysis using whole genome sequencing (WGS) to track disease and to understand the source of local outbreaks (Glaser et al, 2016;Kamath et al, 2016). Its remarkable discriminatory power is useful not only for local disease control, but also to establish and evaluate disease control policies at the national and international level (Kao et al, 2016;Crispell et al, 2017).…”
Section: (79)mentioning
confidence: 99%
“…Recent publications have shown the value of single nucleotide polymorphism (SNP) analysis using whole genome sequencing (WGS) to track disease and to understand the source of local outbreaks (Glaser et al, 2016;Kamath et al, 2016). Its remarkable discriminatory power is useful not only for local disease control, but also to establish and evaluate disease control policies at the national and international level (Kao et al, 2016;Crispell et al, 2017).…”
Section: (79)mentioning
confidence: 99%
“…Sequence analysis tools such as Bayesian Evolutionary Analysis by Sampling Trees (BEAST) utilize the genetic variation present in sets of samples to estimate evolutionary parameters in the context of time and space (Drummond & Rambaut, ; Drummond, Rambaut, Shapiro, & Pybus, ; Drummond, Ho, Phillips, & Rambaut, ; Lemey, Rambaut, Drummond, & Suchard, ). Reconstruction of pathogen genealogies from time‐structured sequence data allows for the estimation of evolutionary substitution rates (molecular clock), which can be used to measure the timing of epidemiologically important events, such as epidemic outbreaks and interspecies transmission (Firth et al, ); they also allow us to study infectious diseases in multi‐host systems and the identification of pathogen reservoirs (Heled & Drummond, ; De Maio, Wu, O'Reilly, & Wilson, ; Kao, Price‐Carter, & Robbe‐Austerman, ). It has been shown that ancestral state reconstruction of pathogen genealogies through phylogenetic trees is a useful tool to address this challenge (Heled & Drummond, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although in many countries bovine TB has been controlled successfully with test and slaughter strategies and movement restriction, control is particularly challenging in countries like NZ in which there is a wildlife reservoir of infection ( 1 , 3 ). In Britain and Ireland the Eurasian badger harbors and spreads M. bovis , in France the wild boar, in Michigan and Minnesota in the USA, deer, and in NZ the brush-tail possum, [reviewed in ( 4 )]. Effective control under these circumstances involves not only test and slaughter and movement control but also knowledge and control of the infection status in wildlife ( 3 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in DNA sequencing have facilitated the routine comparisons of entire bacterial genomes [whole genome sequencing (WGS)] for determining the source of bacterial infections and this technology shows promise in aiding bovine TB control including situations that are complicated by wildlife reservoirs ( 4 , 16 22 ). The single nucleotide polymorphism (SNP) lineages that result from WGS are far superior to the “types” that come from comparing a small number of sites in Spoligo or VNTR typing analyses.…”
Section: Introductionmentioning
confidence: 99%